Exploration of the Phenomenon of Early Marriage in Kampung Badran, Yogyakarta City: A Qualitative Study - Sulistyawati, Erni; Urrahman, Dhiya; Trisnaningsih, Rahma; Sulistyowati, Endang Tri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Data obtained from the DIY Women's Empowerment, Child Protection and Population Control Service shows that in 2019 early marriages reached 394 cases and increased to 948 cases in 2020 with women under 19 years of age. The increasing number of early marriages in the Yogyakarta Region is important to note because Yogyakarta is a destination for students from outside the region to continue their education.Objective: The purpose of this study was to determine the perceptions of female adolescent about early marriage in the Badran Village Area of Yogyakarta City. Method: This study uses a qualitative method with a phenomenological approach. Data collection techniques were carried out through in-depth interviews and Forum Group Discussions (FGD). Research informants consisted of female adolescent and parents who had young daughters.Results: This study resulted in young women's perceptions about early marriage. The causes of early marriage are due to following social media trends, being matched by parents and getting pregnant outside of marriage. The impacts on female adolescent include health impacts, psychological impacts, social impacts, economic impacts and educational impacts. The impacts on parents are that the age difference with their children is not far and they feel calm that their children are married. Efforts to prevent early marriage are carried out by young women, parents, communities and schools.Conclusion: Perceptions of female adolescent about early marriage include the causes of early marriage, the impacts of early marriage, causes of early marriage and efforts to prevent early marriage.